Gummy Smile - Advantages and Disadvantages of Botulinum Toxin Treatment Compared to Orthognathic Surgery - Siew Yong, Tan (Archive of Orofacial Data Science, 2024)
AIM: This narrative literature review aims to evaluate the treatment of botulinum toxin compared to Le Fort I orthognathic surgery in patients with a gummy smile. METHODS: An electronic search was conducted via PubMed/Medline and Google Scholar using keywords such as "gummy smile", "excessive gingival display", "high smile line", "botulinum toxin treatment and correction", "botox usages" and "orthognathic surgery" for studies published until January 2015. After excluding unrelated items, the initial search yielded 84 articles. Following the exclusion of irrelevant articles based on abstract and title, the full texts of 60 articles were reviewed and included in this study. RESULTS: Botulinum toxin treatment and Le Fort I osteotomy present distinct advantages and disadvantages. Botulinum toxin serves as an adjunct for correcting excessive gingival display and is gaining popularity due to its minimally invasive nature. However, Le Fort I osteotomy remains the gold standard for correcting vertical maxillary excess in gummy smile patients. CONCLUSIONS: Both botulinum toxin treatment and Le Fort I osteotomy are essential for correcting different types of gummy smiles. Neither can completely replace the other in the correction of gummy smiles.